2006
DOI: 10.1253/circj.70.376
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Dilated Cardiomyopathy Revisited An Improvement in Survival Over the Past 20 Years

Abstract: diopathic dilated cardiomyopathy had a poor prognosis in the past. [1][2][3][4][5] Many randomized clinical trials performed in the United States of America and Europe have shown the beneficial effects of angiotensin converting enzyme inhibitors (ACEI), [6][7][8][9] angiotensin II receptor blockers (ARB) [10][11][12][13] and blockers on the survival of the patients with congestive heart failure. [14][15][16][17][18][19] In contrast, only 2 small randomized studies of ARB (candesartan) 20 and blocker (carvedilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 38 publications
4
14
0
1
Order By: Relevance
“…A low dose of carvedilol of 5 mg/day was beneficial in Japanese patients with heart failure in the Multicenter Carvedilol Heart Failure Dose Assessment (MUCHA) trial [ 26 ]. We have previously reported that low doses of ACE inhibitors, ARBs, and β blockers had favorable effects on the prognosis of Japanese patients with IDC [ 27 , 28 ]. The Japanese Guidelines (available at the Japanese Circulation Society Web site ( http://www.j-circ.or.jp/ ) have recommended a targeting dose of enalapril of 5 to 10 mg/day and of carvedilol of 5 to 20 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…A low dose of carvedilol of 5 mg/day was beneficial in Japanese patients with heart failure in the Multicenter Carvedilol Heart Failure Dose Assessment (MUCHA) trial [ 26 ]. We have previously reported that low doses of ACE inhibitors, ARBs, and β blockers had favorable effects on the prognosis of Japanese patients with IDC [ 27 , 28 ]. The Japanese Guidelines (available at the Japanese Circulation Society Web site ( http://www.j-circ.or.jp/ ) have recommended a targeting dose of enalapril of 5 to 10 mg/day and of carvedilol of 5 to 20 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…DCM patients develop not only heart pump weakening, but also heart valve problems, blood clots, and arrhythmias leading to heart and secondary organ failures. DCM patients show transplantation-free survival at the rate of 50–60% over 5 years in children (15) and in adults (7, 16, 17), however improved medication can increase the survival rate up to 80% (16). Particularly high mortality has been reported for patients with DCM due to Chagas disease (17).…”
Section: Pathophysiology Of Myocarditis In Humanmentioning
confidence: 99%
“…The DuraHeart is expected to be one of the options for improving the prognosis of severe heart failure patients by enabling reliable long-term circulatory support. 12,13 It is still debatable which type of rotary pump, axial or centrifugal, including the magnetically levitated DuraHeart, is preferable for application in patients requiring higher pump flows and/or long-term support. Recently, some axial pumps have achieved circulatory assistance for more than 2 years.…”
Section: Discussionmentioning
confidence: 99%